2018
DOI: 10.2807/1560-7917.es.2018.23.45.1800201
|View full text |Cite
|
Sign up to set email alerts
|

Tick-borne encephalitis in Europe, 2012 to 2016

Abstract: Since 2012, tick-borne encephalitis (TBE) is a notifiable in the European Union. The European Centre for Disease Prevention and Control annually collects data from 28 countries plus Iceland and Norway, based on the EU case definition. Between 2012 and 2016, 23 countries reported 12,500 TBE cases (Ireland and Spain reported none), of which 11,623 (93.0%) were confirmed cases and 878 (7.0%) probable cases. Two countries (Czech Republic and Lithuania) accounted for 38.6% of all reported cases, although their comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
134
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(150 citation statements)
references
References 31 publications
8
134
2
6
Order By: Relevance
“…An increasing number of human cases of TBE has been recorded in Sweden as TBEV is emerging into new areas and vaccine coverage is incomplete. TBE is emerging into new areas not only in Sweden, but also establishing itself in regions all over Europe and Asia [19,33,34]. The epidemiology of TBE in Sweden has changed over the last 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of human cases of TBE has been recorded in Sweden as TBEV is emerging into new areas and vaccine coverage is incomplete. TBE is emerging into new areas not only in Sweden, but also establishing itself in regions all over Europe and Asia [19,33,34]. The epidemiology of TBE in Sweden has changed over the last 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…TBE is an important and growing public health problem in Europe and Asia [1][2][3][4]. In 2016, France reported a marked increase of TBE cases, following which Sweden reported its highest numbers of TBE cases since 1956 when comparable records were first kept, with 391 and 385 cases during 2017 and 2018, respectively, while in Finland the number of TBE cases has more than doubled during the last decade, fatalities have occurred and the disease has spread to new areas [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Tick-borne encephalitis virus (TBEV) is the most important tick-transmitted virus causing human disease in Europe and Asia [1][2][3][4]. TBEV belongs to the genus Flavivirus, within the Flaviviridae family, and can be divided into three distinct subtypes: the European (TBEV-Eur, formerly known as Central European encephalitis virus), the Siberian (TBEV-Sib, formerly known as Siberian encephalitis virus), and the Far Eastern (TBEV-FE, formerly known as Russian Spring Summer encephalitis virus) subtypes [3].…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, increasing evidence about the occurrence of immunization failure with the TBE virus (TBEV) vaccine. A comprehensive study on TBE in Europe (5205 cases) reported that the condition developed in 87 patients (1.7%) despite those individuals receiving at least two primary vaccination courses [9]. The European vaccines are licensed for adults and children >1 years [6].…”
Section: Introductionmentioning
confidence: 99%